2021
DOI: 10.1007/s10942-021-00429-9
|View full text |Cite|
|
Sign up to set email alerts
|

The Combined Contribution of Fear and Perceived Danger of COVID-19 and Metacognitions to Anxiety Levels during the COVID-19 Pandemic

Abstract: Despite a wide base of research suggesting a major role for dysfunctional metacognitions in contributing to anxiety, their role in explaining psychological distress in the context of the COVID-19 pandemic remains unclear. In this study we investigated whether metacognitions would predict anxiety, while controlling for fear and perceived danger of COVID-19. A total of 862 individuals were included in this study. Participants completed sociodemographic questions, emotional state questions relating to COVID-19, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…Consistently with a previous study (Akbari, Seydavi, et al, 2021 ), we found that participants who perceived themselves to be vulnerable to the COVID‐19, compared with those who did not, had higher levels of C‐19ASS Perseveration and C‐19ASS Avoidance. Being the construct of the COVID‐19 anxiety syndrome conceptually aligned with the Self‐Regulatory Executive Function model (S‐REF) (Wells & Matthews, 1994 , 1996 ), within this theoretical frame, it may be purported that those who perceive themselves to be vulnerable to the COVID‐19 may also hold beliefs about the need to control thinking (metacognitive beliefs) in response to COVID‐19 fear (Akbari, Spada, et al, 2021 ; Aydın et al, 2021 ), that in turn, might increase the likelihood of using dysfunctional coping strategies (Akbari, Spada, et al, 2021 ; Wells & Matthews, 1996 ) such as C‐19ASS Perseveration and C‐19ASS Avoidance. However, the lack of studies exploring this hypothesis prevents us to draw firm conclusions about the relationship between the perception of vulnerability to COVID‐19 and the COVID‐19 anxiety syndrome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistently with a previous study (Akbari, Seydavi, et al, 2021 ), we found that participants who perceived themselves to be vulnerable to the COVID‐19, compared with those who did not, had higher levels of C‐19ASS Perseveration and C‐19ASS Avoidance. Being the construct of the COVID‐19 anxiety syndrome conceptually aligned with the Self‐Regulatory Executive Function model (S‐REF) (Wells & Matthews, 1994 , 1996 ), within this theoretical frame, it may be purported that those who perceive themselves to be vulnerable to the COVID‐19 may also hold beliefs about the need to control thinking (metacognitive beliefs) in response to COVID‐19 fear (Akbari, Spada, et al, 2021 ; Aydın et al, 2021 ), that in turn, might increase the likelihood of using dysfunctional coping strategies (Akbari, Spada, et al, 2021 ; Wells & Matthews, 1996 ) such as C‐19ASS Perseveration and C‐19ASS Avoidance. However, the lack of studies exploring this hypothesis prevents us to draw firm conclusions about the relationship between the perception of vulnerability to COVID‐19 and the COVID‐19 anxiety syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Consistently with a previous study (Akbari, Seydavi, et al, 2021), we found that participants who perceived themselves to be vulnerable to the COVID-19, compared with those who did not, had higher levels of C-19ASS Perseveration and C-19ASS Avoidance. Being the construct of the COVID-19 anxiety syndrome conceptually aligned with the Self-Regulatory Executive Function model (S-REF) (Wells & Matthews, 1994, within this theoretical frame, it may be purported that those who perceive themselves to be vulnerable to the COVID-19 may also hold beliefs about the need to control thinking (metacognitive beliefs) in response to COVID-19 fear Aydın et al, 2021), that in turn, might increase the likelihood of using dysfunctional coping strategies Wells & Matthews, 1996) Finally, exploring differences on C-19ASS on the basis of work status, we found that health care workers had lower levels of C-19ASS Avoidance than the general population. This could be explained by the fact that during COVID-19 pandemic health care workers, due to their role in tackling the COVID-19 pandemic (Busch et al, 2021;Theorell, 2020), have preserved their full/normal functioning (e.g., spending more time outside home, going to work, using public transport, social relationship and being exposed to subjects infected by COVID-19) (Bielicki et al, 2020;Mansueto et al, 2021;Peng et al, 2021;Zhang et al, 2020).…”
Section: Validation Of the Italian Version Of C-19assmentioning
confidence: 99%
“…From this perspective, considering the global scope of COVID-19, it should be regarded not only as a medical health crisis but also as a mental health emergency (Aşkın et al, 2020). Research conducted during previous pandemics and the COVID-19 period has consistently identified widespread feelings of loneliness, anxiety, health concerns, depression, fear, stress, post-traumatic stress symptoms, and avoidance issues across various segments of society (Hawryluck et al, 2004;Wu et al, 2005;Mihashi et al, 2009;Asante, 2012;Aydın et al, 2022;Arslan et al, 2021;Parker et al, 2020;Özdin & Bayrak Özdin, 2020;Lee et al, 2020;Fancourt et al, 2020;Busch et al, 2021;Albery et al 2021;Jones et al, 2023).…”
Section: Introduction the Impacts Of Covid-19 Pandemicmentioning
confidence: 99%